The Impact of Socio-Emotional Learning on School Success and Student Behavior - Marino Marjan Ninčević (Društvene i Humanističke Studije)
This paper provides a detailed examination of the impact of social-emotional learning (SEL) on students’ school performance and behaviour, with a special focus on analysing the integration of SEL programs into the school curriculum. The subject of the paper is aimed at showcasing the benefits that SEL brings to students, ranging from improved school performance to the development of social skills and the reduction of problematic behaviour. The purpose of the research is to highlight the importance of SEL in education while emphasizing key pedagogical and social implications arising from its implementation. The structure of the paper begins with an introduction to the concept of SEL, defining its core components such as self-awareness, self-regulation, social awareness, relationship skills, and responsible decision-making. It then analyses the impact of SEL programs on school performance and student behaviour, highlighting how SEL can significantly reduce problematic behaviours and improve social interactions among students. The paper also addresses the challenges of implementing SEL, including a lack of resources and teacher training, as well as the need for involving parents and the broader community. The paper provides recommendations for further research on the long-term effects of SEL programs, emphasizing that continuous teacher training and active parental involvement are key to the successful implementation of SEL. The pedagogical implications of the study point to the need for the systematic integration of SEL into the education system, which can, in the end, improve students’ school performance and emotional well-being.